Star wars, aftermath [compact disc, unabridged] - Wendig, Chuck (Star wars., 2015)
As the Empire reels from its critical defeats at the Battle of Endor, the Rebel Alliance, now a fledgling New Republic, presses its advantage by hunting down the enemy's scattered forces before they can regroup and retaliate. But above the remote planet Akiva, an ominous show of the enemy's strength is unfolding. Out on a lone reconnaissance mission, pilot Wedge Antilles watches Imperial Star Destroyers gather like birds of prey circling for a kill, but he₂s taken captive before he can report back to the New Republic leaders.